PENGARUH EDUKASI PENCEGAHAN RISIKO JATUH TERHADAP PRAKTIK KELUARGA DALAM MENCEGAH JATUH PADA PASIEN RAWAT INAP DI RSUD KABUPATEN BATANG - Sri Mumpuni Yuniarsih; Prihadi Prihadi; Rahajeng Win Martani (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2021)
Background: prevention of the risk of falling is a form of patient safety for inpatients. This prevention must be the concern of both the nurse and the family. Families need education to obtain information on how to prevent the risk of falling so that they can be implemented properly.  Purpose of the study: to determine the effect of fall risk prevention education on family practices in preventing the risk of falling inpatients at Batang Hospital. Methods: The research design used was a quasy experiment with a one group pre-post test approach. The sample in this study were 86 patients with the risk of falling at the Batang District Hospital. The sampling technique used was accidental sampling technique. The instrument in this study used a check list / observation sheet. The data analysis used was the Wilcoxon test. The results of the study: different test results with the Wilcoxon test with p value: 0.000 which means that there is an effect of prevention education on family practice in preventing the risk of falling in hospitalized patients at RSUD Batang. Good knowledge will also influence good attitudes and actions. Suggestion: Families should practice fall risk prevention to reduce the incidence of falls that cause injury to the patient.